Compensation claims after hip arthroplasty surgery in Norway 2008–2018. (4th May 2021) - Aae, Tommy Frøseth; Jakobsen, Rune Bruhn; Bukholm, Ida Rashida Khan; Fenstad, Anne Marie; Furnes, Ove; Randsborg, Per-Henrik
Abstract : Background and purpose — Orthopedic surgery is one of the specialties with most compensation claims, therefore we assessed the most common reasons for complaints following total hip arthroplasty (THA) reported to the Norwegian System of Patient Injury Compensation (NPE) and viewed these complaints in light of the data from the Norwegian Arthroplasty Register (NAR). Patients and methods — We collected data from NPE and NAR for the study period (2008–2018), including age, sex, and type of complaint, and reason for accepted claims from NPE, and the number of arthroplasty surgeries from NAR. The institutions were grouped by quartiles into quarters according to annual procedure volume, and the effect of hospital procedure volume on the risk for accepted claim was estimated. Results — 70, 327 THAs were reported to NAR. NPE handled 1, 350 claims, corresponding to 1.9% of all reported THAs. 595 (44%) claims were accepted, representing 0.8% of all THAs. Hospital-acquired infection was the most common reason for accepted claims (34%), followed by wrong implant position in 11% of patients. Low annual volume institutions (less than 93 THAs per year) had a statistically significant 1.6 times higher proportion of accepted claims compared with higher volume institutions. Interpretation — The 0.8% risk of accepted claims following THAs is 1.6 times higher for patients treated in low-volume institutions, which should consider increasing the volume of THAs or referring these patients to higher volume institutions.